Orphan works: An examination of Indonesian and Malaysian copyright law - Muhamad Khair, Muhamad Helmi; Barizah, Nurul (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: This paper reports findings from research on orphan works in Indonesia and Malaysia.